IMF Research Bulletin, September 2010. (IMF Research Bulletin; IMF Research Bulletin, 2010)
This paper analyzes transmission of the great recession from advanced to emerging economies. The widespread impact of the global financial crisis of 2008-09 has spurred researchers to examine how the associated recession was transmitted from advanced to emerging economies. Recent IMF studies have found that precrisis vulnerabilities such as large current account deficits, rapid credit growth, and high levels of short-term debt were strongly associated with the magnitude of spillovers. Trade, bank lending, and financial markets served as key transmission channels.